The Inhibition of Interfacial Ice Formation and Stress Accumulation with Zwitterionic Betaine and Trehalose for High-Efficiency Skin Cryopreservation - Xinmeng Liu; Liming Zhang; Haoyue Li; Jing Yang; Lei Zhang (Research)
Cryopreservation is a promising technique for the long-term storage of skin. However, the formation of ice crystals during cryopreservation unavoidably damages skin structure and functionality. Currently, the lack of thorough and systematic investigation into the internal mechanisms of skin cryoinjury obstructs the advancement of cryopreservation technology. In this study, we identified 3 primary contributors to skin cryoinjury: interfacial ice nucleation, stress accumulation, and thermal stress escalation. We emphasized the paramount role of interfacial ice nucleation in provoking ice growth within the skin during the cooling process. This progress subsequently leads to stress accumulation within the skin. During the rewarming process, the brittleness of skin, previously subjected to freezing, experienced a marked increase in thermal stress due to ice recrystallization. Based on these insights, we developed a novel zwitterionic betaine-based solution formulation designed for cryopreservation skin. This cryoprotective agent formulation exhibited superior capability in lowering ice nucleation temperatures and inhibiting ice formation at interfaces, while also facilitating the growth of smooth and rounded ice crystals compared to sharp-edged and cornered crystals formed in aqueous solutions. As a result, we successfully achieved prolonged cryopreservation of the skin for at least 6 months, while preserving 98.7% of structural integrity and 94.7% of Young’s modulus. This work provides valuable insights into the mechanisms of ice crystal damage during organ cryopreservation and profoundly impacts the field of organ transplantation and regenerative medicine.